Systematic student-driven literature reviews in sustainability science – an effective way to merge research and teaching. (15th April 2016) - Luederitz, Christopher; Meyer, Moritz; Abson, David J.; Gralla, Fabienne; Lang, Daniel J.; Rau, Anna-Lena; von Wehrden, Henrik
Abstract: Sustainability science has gained momentum in recent years, with a rising number of publications and degree programs focusing on sustainability. However, sustainability research and sustainability education are often considered as two independent activities within Universities. In this paper we present an educational research approach for integrating teaching and learning settings into academic research. Based on our experience in international research education projects, we present a detailed description of how to empower students to conduct student-driven cutting-edge research that contributes to sustainability science. We established international research education projects with students to jointly conduct, draft and publish systematic literature reviews in sustainability science. Here we present an iterative review procedure for examining qualitative and quantitative data and organizing student-driven research projects. We discuss the demands and limitations of systematic literature reviews in sustainability science and elaborate on the benefits and key challenges from student-driven education research projects. Thus, the paper offers comprehensive guidance to the research community for actively engaging students and junior researchers in collaborative projects to effectively merge research and teaching. In conclusion, we call for stronger integration of students into sustainability research including jointly framing of research projects and collaboratively publishing of research findings in peer-reviewed journals. Highlights: Literature reviews are an effective approach for integrating students into research. A systematic protocol is presented to guide qualitative literature analysis. A detailed description is presented for organizing student-driven research projects. The demands of sustainability science on literature reviews are discussed. Student-driven reviews open the restrictive doors of academia for young scholars.